2023
DOI: 10.3390/nu15051220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Multifunctionality of Soybean Proteins and Peptides in Immune Cell Models

Abstract: Inflammatory and oxidative processes are tightly regulated by innate and adaptive immune systems, which are involved in the pathology of a diversity of chronic diseases. Soybean peptides, such as lunasin, have emerged as one of the most hopeful food-derived peptides with a positive impact on health. The aim was to study the potential antioxidant and immunomodulatory activity of a lunasin-enriched soybean extract (LES). The protein profile of LES was characterized, and its behavior under simulated gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
2
6
2
Order By: Relevance
“…This indicates that a slight enrichment of this peptide was achieved with aqueous solvent extraction. These values were in the range (9.2 to 25.7 mg of lunasin/g of protein) reported for different commercial lunasin-enriched products [36] and were slightly higher than the value recently determined in our laboratory in an albumin-enriched extract [21]. From the starting concentration of 19.45 mg of lunasin/g of protein in LPI, the final LPI-UF2 with a lunasin concentration of 58.2 mg of lunasin/g of protein presented a three-fold enrichment of this peptide.…”
Section: Characterization Of the Lunasin-enriched Soybean Protein Iso...contrasting
confidence: 63%
See 2 more Smart Citations
“…This indicates that a slight enrichment of this peptide was achieved with aqueous solvent extraction. These values were in the range (9.2 to 25.7 mg of lunasin/g of protein) reported for different commercial lunasin-enriched products [36] and were slightly higher than the value recently determined in our laboratory in an albumin-enriched extract [21]. From the starting concentration of 19.45 mg of lunasin/g of protein in LPI, the final LPI-UF2 with a lunasin concentration of 58.2 mg of lunasin/g of protein presented a three-fold enrichment of this peptide.…”
Section: Characterization Of the Lunasin-enriched Soybean Protein Iso...contrasting
confidence: 63%
“…This value was higher than that determined in untreated LPS-challenged cells (29.29 µM). Although lunasin was demonstrated to reduce the NO production induced by LPS in macrophages [ 51 ], our previous study also reported NO-inducing effects in this cell model [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that soybean peptides, such as Lunasin and LES, have the remarkable ability to modulate or regulate both the innate and adaptive arms of the immune system. In essence, they possess the potential to modulate immune responses in different conditions ( 122 ).…”
Section: Immunomodulatory Activity Of Bioactive Peptidesmentioning
confidence: 99%
“…Recent findings revealed that hydrolyzed soy protein containing bioactive lunasin, a 43-amino acid peptide, inhibited LPS-induced secretion of M1-type mediators (IL-1β, IL-6, and NO) through suppressing NF-κB nuclear translocation in RAW264.7 cells (44). Contrary, lunasin enhances phagocytosis and induces the production of M1-type mediators in unstimulated RAW264.7 cells, contributing to the activation of immune responses (45,46) (Table 1). Lunasin also exerts diverse effects on human monocyte-derived DCs, influencing their maturation, M1-type cytokine production, and antigen presentation, which potentiate adaptive immune responses as an adjuvant (47).…”
Section: Bioactive Peptidesmentioning
confidence: 99%